Reason at the Changes Income Taxes in European Union Summary (Research Bulletins of the Faculty of Economic Sciences, 2021)
In last years in European Union observed the tax competition of states, speaking in tendency to reducing the rates of profitable taxes. It speaks many arguments and conducted research for applying linear rates. The height of income taxes has essential influence on enterprises relating the investment, employment and there are their causes in aspiration to maintenance of continuity of power government also.